Toward a Mechanistic Understanding of Color Vision in Insects - Song, Bo-Mi; Lee, Chi-Hon (Frontiers in Neural Circuits, 2018)
Many visual animals exploit spectral information for seeking food and mates, for identifying preys and predators, and for navigation. Animals use chromatic information in two ways. "True color vision", the ability to discriminate visual stimuli on the basis of their spectral content independent of brightness, is thought to play an important role in object identification. In contrast, "wavelength-specific behavior", which is strongly dependent on brightness, often associates with foraging, navigation, and other species-specific needs. Among animals capable of chromatic vision, insects, with their diverse habitats, stereotyped behaviors, well-characterized anatomy and powerful genetic tools, are attractive systems for studying chromatic information processing. In this review, we first discuss insect photoreceptors and the relationship between their spectral sensitivity and animals' color vision and ecology. Second, we review recent studies that dissect chromatic circuits and explore neural mechanisms of chromatic information processing. Finally, we review insect behaviors involving "true color vision" and "wavelength-specific behaviors", especially in bees, butterflies and flies. We include examples of high-order color vision, such as color contrast and constancy, which is shared by vertebrates. We focus on Drosophila studies that identified neuronal correlates of color vision and innate spectral preferences. We also discuss the electrophysiological studies in bees that reveal color encoding. Despite structural differences between insects' and vertebrates' visual systems, their chromatic vision appears to employ the same processing principles, such as color opponency, suggesting convergent solutions of neural computation to common problems.